Menelisik Pertumbuhan Hukum Ekonomi Islam; Sudut Pandang Berbagai Faktor Di Indonesia - Siregar, Indah Permatasari; Khairiyahtussolihah, Assa’adatul (Syekh Ali Hasan Ahmad Addary State Islamic University, 2024)
Starting from the Islamic way of life which also teaches about economics, economic problems arise in Islam. Not only in conventional economics, economic problems arise in Islam, resulting in the decline of Islamic economics. Apart from that, Islamic economics is experiencing growth as a result of the current crisis, this is a reminder for the general public to study Islamic economics, of course the presence of Islamic economics is a source of hope for many people. Because Islamic economics has many benefits for the entire community and will continue through education and gradual steps. The purpose of this study is to examine the factors that influence the growth of the Islamic economy in Indonesia Library research is the search for research data or information through reading scientific journals, reference books, published economic growth reports, and other publications that support this writing. The data used is secondary data derived from a variety of relevant literature. To answer research questions, many sorts of data and information are evaluated and synthesized. The study's findings reveal that human capital, the number of people on the planet, the amount of available land, the number of syariah firms, and the availability of technology all have an impact on economic growth.